Arquitectura e jogo digital. Intersecção e especificidade - José Filipe de Oliveira Pereira (2013)
This research proposes an analysis of the parallelism and intersection of space, form and experience modeling practices across physical and virtual, immersive and interactive, environments. The progressive fusion of material and immaterial precipitates the dilution of the boundaries in the definition of architecture and game design. Disciplines conventionally considered exclusive of distinct dominions of the real are focus of a necessary reform. In the physical realm there must be a rethinking of the traditional methodology of architectural practice, the manufacturing processes, and programmatic responses. How can I enhance the influence of virtual experiences, know-how and hardware behind their development, in more fluid and flexible physical spaces, able to assume a more reactionary position in contact with the user? How do I plan integration and response to the new technological constraints and requirements of the social dynamics increasingly divided between realities? In the virtual realm the popularization of immaterial space featured by the universe of digital games, the progressive development of immersive experiences and the increased supply of new interfaces, trigger the renewed interest in the connections man/machine/avatar. Can the contribution of architectural thinking in virtual space conformation and function strengthen this relationship and deepen the degree of immersion?